The Effect of Haruan (Channa striata) Fish Bone Powder Supplementation during Pregnancy and Lactation on the Mineral Levels of Jaws and Teeth of Rat Offspring: The Effect of Haruan (Channa striata) Fish Bone Powder Supplementation during Pregnancy and Lactation on the Mineral Levels of Jaws and Teeth of Rat Offspring - A.M, Shaikh (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Haruanfish (Channa striata) is an endemic fish of Kalimantan that is widely used by the people in South Kalimantan Province. Haruan fish bone waste can be used for additional nutrition in pregnant women and can support the process of bone and teeth remineralization. Haruan fish bones contain minerals in the form of calcium, phosphorus, fluoride and magnesium. Purpose:this study was conductedinvestigatethe effect of Haruan (Channa striata) fish bone powder during pregnancy and lactation on the mineral levels of jaws and teethof Wistar rat (Rattus norvegicus)offspring. Methods:This study used a true experimental design with a Post Test Only Control Group Design. Group 1 (treatment) were given Haruan fish bone powder (Channa striata) and group 2 (control) without haruan fish bone powder (Channa striata)from the fist pregnancy up to 22 days after the delivery. The calcium, phosphorus, fluoride and magnesium level of the jaws and teeth of the pups from both groups were assayed and analyzed. Results:Statistictest result showed a difference in mineral levels in rat pups the jaw and teeth between the control and the treatment group. Conclusion:There was an effect of giving Haruan fish bone powder (Channa striata) during pregnancy and